Change of Rural Development Policy in South Korea after Korean War - Lee In-hee (Journal of Regional and City Planning, 2021)
The industrial development of South Korea is an exceptional success story. However, there were several side effects of the strong economic growth, such as rapidly increasing city populations and severe socio-economic inequality. The population in the area of the capital currently amounts to half of the national population of South Korea. The Korean government has implemented various regional development policies for a more balanced national development. This paper investigates the series of Five-Year Economic Development Plans from 1962-1997 and the Saemaul Undong movement, who contributed to the record of economic development of South Korea, and discusses the rural development policies recently promoted by the South Korean government to address problems such as the progressive decrease and stagnation of agricultural productivity, the depopulation and aging trends in rural areas, the deterioration of farm household income structure, and import expansion and unstable grain supply by free trade agreement.   Abstract. Perkembangan industri Korea Selatan adalah kisah sukses yang luar biasa. Namun, ada beberapa efek samping dari pertumbuhan ekonomi yang kuat, seperti populasi kota yang meningkat pesat dan ketimpangan sosial ekonomi yang parah. Penduduk di wilayah ibu kota saat ini berjumlah setengah dari penduduk nasional Korea Selatan. Pemerintah Korea telah menerapkan berbagai kebijakan pembangunan daerah untuk pembangunan nasional yang lebih seimbang. Makalah ini menyelidiki serangkaian Rencana Pembangunan Ekonomi Lima Tahun dari 1962-1997 dan gerakan Saemaul Undong, yang berkontribusi pada rekor pembangunan ekonomi Korea Selatan, dan membahas kebijakan pembangunan perdesaan yang baru-baru ini dipromosikan oleh pemerintah Korea Selatan untuk mengatasi masalah-masalah seperti sebagai penurunan progresif dan stagnasi produktivitas pertanian, depopulasi dan tren penuaan di daerah perdesaan, kerusakan struktur pendapatan rumah tangga pertanian, dan ekspansi impor dan pasokan biji-bijian yang tidak stabil oleh perjanjian perdagangan bebas.   Keywords. Saemaul Undong, perencanaan penggunaan lahan, pembangunan perdesaan, pembangunan ekonomi, perubahan populasi.